Attitudes to Medication after Kidney Transplantation and Their Association with Medication Adherence and Graft Survival: A 2-Year Follow-Up Study. (28th April 2014) - Tielen, Mirjam; van Exel, Job; Laging, Mirjam; Beck, Denise K.; Khemai, Roshni; van Gelder, Teun; Betjes, Michiel G. H.; Weimar, Willem; Massey, Emma K.
Abstract : Background . Nonadherence to medication is a common problem after kidney transplantation. The aim of this study was to explore attitudes towards medication, adherence, and the relationship with clinical outcomes. Method . Kidney recipients participated in a Q-methodological study 6 weeks after transplantation. As a measure of medication adherence, respondents completed the Basel Assessment of Adherence to Immunosuppressive Medications Scale (BAASIS © -interview). Moreover, the intrapatient variability in the pharmacokinetics of tacrolimus was calculated, which measures stability of drug intake. Data on graft survival was retrieved from patient records up to 2 years after transplantation. Results . 113 renal transplant recipients (19–75 years old) participated in the study. Results revealed three attitudes towards medication adherence—attitude 1: "confident and accurate, " attitude 2: "concerned and vigilant, " and attitude 3: "appearance oriented and assertive." We found association of attitudes with intrapatient variability in pharmacokinetics of tacrolimus, but not with self-reported nonadherence or graft survival. However, self-reported nonadherence immediately after transplantation was associated with lower two-year graft survival. Conclusion . These preliminary findings suggest that nonadherence shortly after kidney transplantation may be a risk factor for lower graft survival in the years to follow. The attitudes to medication were not a risk factor.